Pengaruh Metode Pembelajaran Problem Solving terhadap Kemampuan Berpikir Kritis Matematika - Noni Rahmawanty (JKPM (Jurnal Kajian Pendidikan Matematika), 2017)
The research is aimed to determine and answer the problems about The impacts of problem solving learning method on mathematics critical thinking ability. The method is used in this research is experiment method with quantitative, and the analysis used t test. The sample is the students grade x about 30 students is taken from each class by proportional random sampling. Based on normality test through liliefors test both of class in normal distribution and homogeneity test used f test and both of class is homogen. The result of hypothesis test show that t test (5.093) ? t table (2.002), it means that problem solving method in SMK Islam Wijaya is more influence on mathematics critical thinking ability than problem solving based on learning method.